Teaching work during the COVID-19 pandemic challenges and learning - Lisbon , Fernanda Cordeiro; Quirino , Raquel (Seven Editora, 2023)
During the COVID-19 pandemic outbreak, several changes have become necessary in the world of work, especially regarding the modalities and spaces of its realization. Due to the need for social isolation to minimize the spread of the virus and the consequent contamination of the mass population, the implementation of remote work performed at home, mediated by digital technologies - the so-called home office - has been implemented in several professional areas. In this way, the public and external space, in which productive and salaried work takes place, migrated to the private space, in which unpaid work is performed and dedicated to the reproduction of the conditions of existence, domestic work. Two distinct environments, in which the sexual division of labor and the social relations of sex/gender develop, have been transformed into one. Specifically in the teaching work in Basic Education, despite its already proclaimed precariousness, devaluation, and feminization, the implementation of Emergency Remote Teaching (ERE) added to the overload of the teacher-mother-wife-housewife woman with the realization of a distance educational practice, mediated by unusual digital technologies in public schools, as well as the unforeseen intertwining of their public and domestic work spaces. Unveiling how this moment was experienced by the teachers, its impacts, challenges and difficulties, strategies of resistance and coping, in the face of multiple and simultaneous works, the unusual transformation of their public and private spaces into one, and the compulsory need to use Digital Information and Communication Technologies (DICT) in the educational process, is what this article addresses. It seeks to understand and rethink the training and teaching work in the face of unforeseen situations, the compulsory and unplanned use of digital technologies as tools for teaching-learning, and the sexual division of the domestic work of teachers. The theoretical-empirical research had a qualitative approach, whose subjects are teachers of Basic Education who work in Cycles I and II, of the Municipal Public Education Network of Belo Horizonte, who were interviewed in person using a semi-structured script. Subsequently, excerpts from the interviewees' speeches, which help to answer the research questions, were selected and analyzed in the light of the theories on Teacher Education and Work and Sexual Division of Labor.DOI:https://doi.org/10.56238/emerrelcovid19-051